Dimensi Ekonomi dalam Haji dan Umrah: Kajian Interdisipliner dengan Pendekatan Tafsir dan Ekonomi - Muhammad Fadhil Fathoni; Mohamad Zaenal Arifin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to examine the economic dimensions embedded in the rituals of Hajj and Umrah, which have often been overlooked due to a dominant understanding that views both solely as spiritual activities. Employing a qualitative library research method with a descriptive-analytical approach, this study investigates three main aspects: the concept of istiṭā‘ah (financial capability) and its relation to opportunity cost and the prioritization of needs (ikhtiyār); the legitimacy of trade activities during the Hajj season based on Qur’anic evidence and exegesis; and the economic impact of Hajj and Umrah on both micro and macro sectors through the multiplier effect theory. Primary sources include Qur’anic verses and classical exegeses such as those by Ibn Kathīr, al-Baghawī, and al-Wāḥidī, as well as the jurisprudence of the four schools, while secondary sources consist of Islamic economic literature, conventional economic theory, and empirical data from the Hajj industry. The findings reveal that istiṭā‘ah serves as a standard of financial readiness, requiring a surplus of wealth that covers travel expenses, family maintenance, and debt settlement, thereby reflecting the principles of opportunity cost and the Islamic ethics of prioritizing needs. The study also confirms the explicit legitimacy of conducting business during Hajj as stated in QS. al-Baqarah/2:198, demonstrating that Islam does not separate spiritual devotion from economic productivity. Furthermore, the economic impact of Hajj and Umrah generates a significant multiplier effect, driving growth across 11 major sectors—such as transportation, hospitality, food and beverages, and micro-enterprises—with total expenditures reaching 47 billion Saudi Riyals in 2020. This multiplier mechanism spreads income from a single initial expenditure throughout various sectors in a chain reaction, resulting in a multiplied increase in national income. The study concludes that Hajj and Umrah are not merely spiritual obligations, but also comprehensive instruments of economic empowerment that reflect the holistic integration of worship and economic well-being in Islam.